2013
DOI: 10.1016/j.jet.2013.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Optimal redistributive taxation with both extensive and intensive responses

Abstract: We derive a general optimal income tax formula when individuals respond along both the intensive and extensive margins and when income effects can prevail. Individuals are heterogeneous across two dimensions: their skill and their disutility of participation. Preferences over consumption and work effort can differ with respect to the level of skill, with only the Spence-Mirrlees condition being imposed. Employing a new tax perturbation approach that integrates the nonlinearity of the tax function into the beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
173
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(181 citation statements)
references
References 42 publications
(105 reference statements)
7
173
1
Order By: Relevance
“…This division barely changes over time. Interestingly, some PTRs in the bottom decile are negative in 2006 which coincides with the theoretical results of Diamond (1980), Saez (2002) and Jacquet et al (2013). This is due to the additional child benefit (Kinderzuschlag) which is an in-work benefit introduced in 2005 to raise the household income of working families above the threshold of social assistance.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…This division barely changes over time. Interestingly, some PTRs in the bottom decile are negative in 2006 which coincides with the theoretical results of Diamond (1980), Saez (2002) and Jacquet et al (2013). This is due to the additional child benefit (Kinderzuschlag) which is an in-work benefit introduced in 2005 to raise the household income of working families above the threshold of social assistance.…”
supporting
confidence: 80%
“…In optimal tax theory, work incentives inherent in the tax-benefit system are captured by the Effective Marginal Tax Rate (EMTR) at intensive margin and the Participation Tax Rate (PTR) at the extensive margin. Diamond (1980), Saez (2002) and, more recently, Jacquet et al (2013) find that the optimal PTR can be negative for lower income levels. The empirical literature has shown that the behavioral response at the extensive margin exceeds the response at the intensive margin.…”
Section: Literature Reviewmentioning
confidence: 97%
“…3 Another interesting crosscountry application of the inverse-taxation methodology is Spadaro et al (2015), with a focus on the poverty-aversion of European policy-makers. 4 Zoutman et al (2014) analyze the re-distributive preferences in the Netherlands by inverting the continuous optimal income tax model with both intensive and extensive margins developed by Jacquet et al (2013). Relatedly, Zoutman et al (2015) and Jacobs et al (2017) analyze the political preferences for redistribution of Dutch political parties.…”
Section: Related Literaturementioning
confidence: 99%
“…13 The key intuition behind this equation is that it trades off the mechanical increases in tax revenue resulting from increases in taxes on the working population against the behavioral losses in tax revenue resulting from participation responses. As explained in Jacquet et al (2013), in the presence of intensive-margin responses [ε(z) = 0], optimal participation taxes will deviate from formula (5) since one needs to take into account the distortions induced by the tax schedule on intensive-margin responses. 14 In the presence of intensive-margin responses, Eq.…”
Section: Intensive and Extensive Marginmentioning
confidence: 99%
See 1 more Smart Citation